SEARCHING FOR A NEW METHOD IN HISTORICAL STUDIES: THE SOURCES IN OTTOMAN TURKISH AND INTERDISCIPLINARY APPLICATION - Serhat KÜÇÜK (Fırat University, 2019)
The primary sources is a basic element giving original and scientific identity to historical research. Utilization of the primary sources depends on their classification and storing according to certain rules. The archives are the places where this storing is done. However, only storing is not enough, how the primary sources are presented to the researchers intended for education and training or the production of scientific knowledge are also important. Starting point of this article is the fact that the presentation is the main determinant from the audience using this sources to fields where the sources are used, but in our country, because of ignoring this quality, the presentation is not given importance as it deserves. Therefore, it is believed that if the ideal presentation is found/applied or if a new communication system between the sources and researchers is established, the historical materials can surmount over the limitations in existing contact and the field. In other words, this method is to provide a reliable ground for the sources in Ottoman-Turkish, which can potentially be used in social sciences as sociology, psychology, philosophy, communication science as media and journalism, sciences as physics, chemistry, biology and medicine, are to analyzed by the scientists of related fields. By the ideal application on the one hand, in general, primary sources which are very important for history are become interdisciplinary, by means of which the sources can be presented more functional than present way of presentation, on the other a new method for transmitting the historical sources to the future generations will be produced through the periodicals. In this context, the axis of this study designated as periodicals and in Turkey, the institutions providing the service of procurement of periodicals are analyzed and the aspects of their presentations are shared. After the presentation of current situation in this institutions, how the shortcomings criticized in the article are resolved on the example of kaynakca.info by means of an application.